Investigation of bushing dimensions and micro hardness changes in thermal friction drilling process - Ozek, Cebeli; Bal, Muhammet (Gazi Univ, Fac Engineering Architecture, 2021)
Friction drilling is a hole drilling method with the effect of heat caused by friction on a work piece-tool interface with a rotating tool. The purpose of this method is to increase the length of the connection for the bushing formed on the wall and the lower part of the hole in the thin-walled sheet. For the study, A7075-T651 alloy and St37 steel sheets have been selected with thickness for t=2-10 mm, which are commonly used in the automotive and aerospace industries. Experimental studies were carried out on the TYT400 milling machine at a speed of n=1120 rpm and f25 mm/min. Specially manufactured high speed steel (HSS) and tungsten carbide (WC) tools were used, the tool profile with conical angle of theta=36 degrees and the tool profile with diameters for empty setd=5, empty setd=10, empty setd=15, empty setd=20 mm. Since St37 steel is ductile, there is not much change in the shape of the bushing with the change of rotational speed and feed rate. On the other hand, A7075-T651 aluminium alloy has a crown-shaped sleeve structure, in which the connection length has increased too much and the crack is dense. In ductile materials, a bushing with a cylindrical length that is suitable for its purpose and increasing the connection length is formed. In the ductile materials, a bushing in the form of excessive cylindrical length and increasing the connection length was obtained. It was determined that a bushing cannot be obtained as desired in brittle materials. It has been observed that the tool diameter and material thickness have a significant effect on the bushing wall thickness, the bushing height and micro hardness.
Termal sürtünmeli delme işleminde oluşan kovan boyutları ve mikro sertlik değişimlerinin araştırılması
Keywords: Friction drilling; Bushing height; Bushing wall thickness; Micro hardness